Implementation Economic Order Quantity and Reorder Point Methods in Inventory Management Information Systems - Setyadi, Heribertus Ary; Al Amin, Budi; Widodo, Pudji (Journal of Information Systems and Informatics, 2024)
Inventory control is at the core of supply management to balance inventory needs and demand. With an inventory system, management can control stock of materials and goods, production process and sales transactions can even stop the production process if necessary. Sari Gamping building materials store that sells various building needs including building materials and tools. Data management of goods, transactions and inventory processing still uses conventional methods using Microsoft Office. The purpose of this research is to analyze the ongoing inventory management process to create an inventory management information system so that it can help the Sari Gamping store in controlling inventory. The Economic Order Quantity (EOQ) and reorder point methods were chosen to optimize inventory to avoid shortages or excess inventories, to fulfill customer orders, to achieve cost efficiency and to prevent problems that may occur. The developed system can manage data on goods, categories, suppliers, manage purchase and sales transactions and can generate information from EOQ calculations, safety stock and reorder points. From the results of testing the calculations of the two methods used with 15 samples of catylac paint variants, the average inventory cost saving in June 2023 was 65.33%.